V.I.P. (Very Impostor Person) : o embuste no acesso às Salas VIP de aeroportos - Niero, Gustavo Luiz (2020)
VIP airport lounges are venues provided aiming to offer comfort to air travel passengers. The exclusive access and outstanding sophistication in such places evoke distinguishable social atmosphere clearly noticeable by consumers. The practice of deviance to the access to VIP lounges is a silent reality and involves luxury, consumer experience and misbehavior concepts. The aim of this research is to understand the VIP lounge access trespassers through the optical of theoretical foundations. Based on in-depth interview analysis with individuals who admitted accessing such venues via non-conventional manners led to the understanding of such phenomenon and the observation of possible consequences to the sponsoring companies to VIP lounges at airport terminals.